1993
DOI: 10.2337/diab.42.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Hormonal Counterregulation, Symptom Awareness, and Neurophysiological Function After Recurrent Short-Term Episodes of Insulin-Induced Hypoglycemia in IDDM Patients

Abstract: To test the hypothesis that recurrent short-term hypoglycemic episodes may impair hormonal counterregulation, symptom awareness, and neurophysiological function during subsequent hypoglycemia, we examined two groups of IDDM patients (n = 18), neither of whom exhibited signs of autonomic neuropathy. Two sequential euglycemic-hypoglycemic clamp studies were performed three days apart with stable glycemic plateaus of 5.6, 3.3, 2.2, and 1.7 mM, at which the patients' awareness of and response to hypoglycemia was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 0 publications
4
27
0
Order By: Relevance
“…Previous studies (12)(13)(14)(15)(16)(17)(18) investigating symptomatic responses to recurrent hypoglycemia did not focus on feelings of hunger. Typically, data on hunger ratings were not analyzed separately but were pooled with rating scores of other hypoglycemic symptoms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies (12)(13)(14)(15)(16)(17)(18) investigating symptomatic responses to recurrent hypoglycemia did not focus on feelings of hunger. Typically, data on hunger ratings were not analyzed separately but were pooled with rating scores of other hypoglycemic symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, hunger may occur at higher plasma glucose levels in those patients than in healthy subjects and may be increased during plasma glucose-lowering therapies. On the other hand, repeated episodes of low plasma glucose have been shown to decrease plasma glucose thresholds for hormonal counterregulation and symptoms (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), suggesting a rapid adaptation of the brain to such conditions. Whether a similar adaptation also exists in regard to feelings of hunger is not known.…”
Section: Any Factors Involved In the Regulation Of Bodymentioning
confidence: 98%
“…Improvement of symptom awareness comprised the overall perception of symptoms and, more specifically, the autonomic symptoms of heart pounding and sweating. Adaptation to recurrent hypoglycemic episodes has recently been shown in nondiabetic subjects (1) and IDDM patients (3,5). In fact, Lingenfelser et al (3) demonstrated that alterations of neuroendocrine counterregulation and symptom perception do occur within 2 days after three short-term hypoglycemic events (<2.2 mmol/1).…”
Section: Conclusion-our Present Datamentioning
confidence: 98%
“…E vidence has emerged in healthy subjects (1,2) and diabetic patients (3)(4)(5) that recurrent short-term hypoglycemic episodes compromise hormonal counterregulation and symptom awareness during subsequent hypoglycemia. The question arises as to whether such defective responses may be improved or even restored (6).…”
mentioning
confidence: 99%
“…Thus, acute deteriorations of glucose homeostasis are likely to cause an instant, but temporary, impairment of cerebral functions (1)(2)(3). Recurrent hypoglycemic episodes over days were also shown to reversibly impair cerebral function, as assessed from neurophysiological measurements (4). Chronic hyperglycemia prevails in IDDM; thus, long-term changes caused by glucotoxicity are likely to occur in brain morphology (5).…”
mentioning
confidence: 97%